Matrix - Silver, Joel; The Wachowski Brothers; The Wachowski Brothers (Warner Home Video, 1999)
Neo (Keanu Reeves) believes that Morpheus (Laurence Fishburne), an elusive figure considered to be the most dangerous man alive, can answer his question -- What is the Matrix? Neo is contacted by Trinity (Carrie-Anne Moss), a beautiful stranger who leads him into an underworld where he meets Morpheus. They fight a brutal battle for their lives against a cadre of viciously intelligent secret agents. It is a truth that could cost Neo something more precious than his life.